Computational investigation to interpret the reacting flow conditions for two different fuels in the scramjet combustor - Namrata Bordoloi; Krishna Murari Pandey; Mukul Ray; Kaushal Kumar Sharma (Results in Engineering, 2022)
The scramjet engines use the atmospheric oxygen to complete the combustion process, therefore, known as Air breathing engines. It does not bear any active parts and operates at supersonic speed, so it becomes essential that the variables such as fuel, pressure, temperature, Mach number to create the necessary environment to initiate the combustion phenomenon. The supersonic combustion undergoes severe turbulence in the variables associated with combustion. Thus, the selection of the appropriate parameters in designing of a suitable combustor is indispensable. The research paper discusses the effects of two different fuel jets on the flow variables in a scramjet combustor under reacting flow conditions. The Computational Fluid Dynamics (CFD) simulations on the scramjet combustor are carried out using Ansys 15.0 software. To investigate the effect of fuels on the combustion characteristics, the effect of pressure, Mach number and species concentration are studied. The pressure distribution for both the fuels shows that the maximum pressure is seen for hydrogen fuel at Mach number 2.52. The Mach number contours for both fuels reveal that the recirculation zone formation is more pronounced for ethylene fuel. The performance assessment of the combustor show that the maximum combustion efficiency was 87.62% and 89.26% and mixing efficiency was 98.97% and 97.46% for hydrogen and ethylene fuel respectively at M-2.52. Thus, it is concluded that the current scramjet model operated more effectively at Mach 2.52 with hydrogen as a fuel.